EDUCATIONAL PSYCHOLOGY CURRICULUM TO IMPROVE STUDENTS' MENTAL WELL-BEING IN SCHOOLS - I Dewa Ayu Eka Purba Dharma Tari; I Gusti Putu Suharta; I Wayan Widiana; I Wayan Lasmawan (Program Studi PGSD Universitas Flores, 2025)
Increased awareness of the importance of mental well-being as a crucial factor in students' academic and personal development demonstrates the need to integrate psychology education into the school curriculum. This study aims to examine the effectiveness of the educational psychology curriculum designed to improve students' mental well-being. Using a systematic review approach using the PRISMA method, this study synthesizes the existing literature on the impact of psychology education in schools. The findings of the study show that the integration of mental health literacy, stress management techniques, and social-emotional learning (SEL) in the school curriculum significantly improves students' emotional resilience, reduces academic stress, and builds positive interpersonal relationships. The curriculum also plays an important role in the early identification of mental health problems and offers effective preventive measures. The novelty of this study lies in its comprehensive approach, which includes trauma-based treatment, mindfulness techniques, and a collaborative model involving teachers, mental health professionals, and families. This research emphasizes the importance of ongoing professional training for educators as well as interdisciplinary collaboration to ensure the effective implementation of mental health support in educational settings. The study advocates the integration of these practices into the standard curriculum to support students' mental well-being and academic success in the long term.